Na marginesie i wokół zagadkowego rebusu z 1621 roku = On the margin and around of the mysterious rebus from 1621 - Sztyber, Radosław (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article attempts to present an old Polish print entitled "Fresh Talks on the News from Ukraine, from Hungary and from Turkey" [Rozmowy świeże o nowinach z Ukrainy, z Węgier i z Turek] and its major as it may be believed secret. The abovementioned leaflet is known by a few specialists, and its previous descriptions seem to be inappropriate because of some quite obvious mistakes concernig i.a. the number of debaters or the time of this written relics publication.
Keywords: polska literatura okolicznościowa XVII wieku; wojna chocimska - 1621; rebus; Łaszcz, Samuel (1588-1649); Polish occasional literature of XVII century; Khotyn war - 1621